The Analysis of the Correlations between BMI and Body Composition among Children with and without Intellectual Disability - Bogdan Constantin Ungurean; Adrian Cojocariu; Beatrice Aurelia Abalașei; Lucian Popescu; Alexandru Rares Puni; Marius Stoica; Carmen Pârvu (MDPI AG, 2022)
Background: Compared to the great volume of studies focusing on children and adolescents without intellectual disability, research regarding body mass index among young populations (13-17 years old) with intellectual disability is scarce, mostly when we refer to the comparisons between various degrees of intellectual disability and gender. Methods: The purpose of this study was to assess a series of morphofunctional parameters among children with and without intellectual disability to characterise the morphofunctional normality and its perturbations. Within the study, we included 101 subjects from several educational institutions, distributed on five groups, by their gender and degree of intellectual disability. Results: The average values of body mass index exceed the values recommended by the WHO among all the five groups (boys and girls with and without intellectual disabilities) prone to obesity. Upon analysing the values of BMI by gender and type of intellectual disability, we note that the prevalence of obesity among boys is 28.07% (BMI > 24), while 19.29% are overweight (BMI ranging between 21.5 and 24). Conclusions: The prevalence of excess weight and obesity among persons with intellectual disabilities was similar among the male and female subjects. It shows an increasing trend by age.